2020
DOI: 10.1051/e3sconf/202015401005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of possibilities of using biomass from cherry and morello cherry stones for energy purposes

Abstract: Growing demand for energy and care about natural environment is the motivation to find alternative sources of energy. One of them is biomass from cherry and morello cherry stones, which is food processing industry waste. Stones have fairly good physical properties regarding material for combustion. Cherry and morello cherry crop in Poland is at the level of 200 thousand tons yearly, and processing them generates a considerable amount of waste that consists of stones, which may be used for energy purposes. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Table 1 shows the basic properties of olive stones. The obtained results indicate that the share of the stone in the weight of the whole fruit is significant and amounts to 17.1% for green olives and 16.5% for dark olives, which is a significant value compared to, e.g., cherry stones, where the share of the stone in the fruit is 9.9% [8]. Olive stones are a waste material, and their management can be problematic.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Table 1 shows the basic properties of olive stones. The obtained results indicate that the share of the stone in the weight of the whole fruit is significant and amounts to 17.1% for green olives and 16.5% for dark olives, which is a significant value compared to, e.g., cherry stones, where the share of the stone in the fruit is 9.9% [8]. Olive stones are a waste material, and their management can be problematic.…”
Section: Resultsmentioning
confidence: 93%
“…No significant influence of the type of olive stone on the drying process was observed for the examined green and dark olive stones (Figure 1d). The ash content of the green olive seeds (Table 1) under investigation was 2.18% and 2.69% of the black olive, which is a relatively high value compared to cherry pits, which contain about 0.25% ash [8], or to nut shells: peanuts, hazelnuts, walnuts, pistachios, which contained, respectively: 2.00%; 0.74%; 1.38%; 1.42% of ash [9]. The heat of combustion of the tested olive seeds is comparable to other biological materials and was 20.64 kJ/g for green olive seeds and 20.07 kJ/g for dark olive seeds.…”
Section: Resultsmentioning
confidence: 95%
“…Considering the results obtained, it can be concluded that apple pomace is characterized by a rather high heat of combustion of about 20 kJ/g ( Table 1 ). For comparison, the heat of combustion of apricot kernels is almost 22 kJ/g [ 35 ], straw is about 18 kJ/g [ 36 ], wood is 16–21 kJ/g, and peat is 16 kJ/g [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage share of cellulose, hemicellulose and lignin in a given type of biomass may vary, which significantly affects its energy parameters and the possibility of using it for the production of biofuels [5]. Depending on the origin of the biomass (classification according to ISO 17225-1:2014 [6]), research is carried out on woody [7][8][9], and herbaceous biomass [10,11], but also pomaces, fruit stones, kernel shells and other residuals [12][13][14][15], and recently on so-called water biomass, or algae, for example, hyacinths [16,17].…”
Section: Introductionmentioning
confidence: 99%